Suplementasi Butirat dan Modulasi Epigenetik melalui Inhibisi Histon Deacetylase pada Diabetes Melitus Tipe 2: Suatu Tinjauan Naratif dengan Perspektif untuk Indonesia - Ainaputri , Aliza Salsabila; Kasasiah, Ahsanal; Malau , Jekmal; Aprillia , Cantika; Siboro , Dewi Pratiwi Purba; Apriyanti , Endeh; Nugraha , Afif Tri (Journal of Pharmaceutical and Sciences, 2026)
Type 2 diabetes mellitus is a multifactorial metabolic disorder characterized by insulin resistance, chronic inflammation, and epigenetic dysregulation. Emerging evidence indicates that butirat supplementation may improve metabolic homeostasis through histon deacetylase inhibition and modulation of gene expression involved in insulin signaling and inflammatory pathways. This review aims to evaluate preclinical and clinical evidence on the role of butirat as an epigenetic modulator in type 2 diabetes mellitus and to discuss its translational relevance, including perspectives for Indonesia. A structured literature search was conducted to identify original research articles published between 2015 and 2025. The selected studies demonstrate that butirat enhances insulin sensitivity, improves glycemic control, and attenuates inflammatory responses through increased histon acetylation. However, direct clinical evidence remains limited. In Indonesia, available data are largely derived from dietary or probiotic interventions that increase endogenous butirat production. Therefore, well designed controlled clinical trials are required to evaluate the therapeutic potential of direct butirat supplementation in populations with type 2 diabetes mellitus.